The determinants of credit restrictions and their impact on micro firms: the case of Colombia - Mora, Jhon James; Espada Castro, Andres David (Emerald Publishing Limited, 2024)
Purpose This article analyzes the determinants of credit constraints and their effects on the productivity of micro-firms in Colombia. Design/methodology/approach An Endogenous Switching Regression Model (ESRM) is estimated to analyze credit constraint impact on economic performance. Findings The results show that owner characteristics such as age and gender decrease the likelihood of being constrained. Firms' characteristics, such as legal status, the formality of the employees, commercial property and savings, are important for reducing credit constraints. Originality/value This article discusses how formal credit restrictions harm the economic performance of Colombia's micro-firms. The results show that the productivity of the micro firms in Colombia could increase, on average, by U$ 825 USD when all types of restrictions are eliminated.